Effect of administration two doses of Human chorionic gonadotropin and combination between human chorionic gonadotropin and flunixin meglumine on pregnancy rates in repeat breeders cross breed cows. - Jawad K. Taher; Khawla A. Hussein (University of Thi-Qar Journal of agricultural research, 2021)
The aim of the current study is to treat cases of repeat breeder in crossbreed cows and to improve pregnancy rate in affected cows. The study divided the number of animals into four groups, group (10 = T1), where the first group gave human chorionic gonadotropin on the day of oestrus and repeated the same dose 1500 IU Five days postinsemination and the group (T2 = 10) where the hCG hormone was given at a dose of 1500 IU on the day of the estrus and Flunxin meglumine treatment with a dose (2ml / 50 kg b.w) each ml contain to (50mg of FM) from the fifth day post insemination for three days and the third group, which numbered 5 cows in the group (C1 = 5), were considered a control group without treatment, while the fourth group(C2=5) is considered fertile cows, the purpose of their presence in the study is to evaluate the effectiveness of the fertility of the semen straws used in the study. The study showed that the pregnancy rate in cows in the groups, respectively, is 40%, 60%, 0%, 60%. The statistical analysis showed that there were significant differences at (P˂0.01) between the treated and fertile groups and the untreated group, which means an improvement in the pregnancy rate in treated cows that were suffering from repeat breeding. Early pregnancy was diagnosed rectally using ultrasound